2020
DOI: 10.1002/jpen.1959
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of Body Mass Index Cutoff Values Used in the Global Leadership Initiative on Malnutrition Criteria for Discriminating Severe and Moderate Malnutrition Based on In‐Patients With Pneumonia in Asians

Abstract: Background This study aimed to investigate the predictive validity of the previously reported body mass index (BMI) cutoff values of the Global Leadership Initiative on Malnutrition (GLIM) criteria for patients with pneumonia in Asians, using a nationwide registry database. Methods The study included 26,098 (2282 patients aged <70 years and 23,784 patients aged ≥70 years) patients with pneumonia aged ≥65 years who were enrolled in the Japan Medical Data Center database between April 2014 and December 2018. Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Within healthcare system outcomes, mortality was reported most frequently (n ¼ 33; 27%) [16,22,23,25,26,28e31, 34,37e42,44,45,53,55,57,60,61,65,67,68,73e75,80,83,85,89]. Other outcomes were hospitalization/readmissions/costs (n ¼ 11; 9%) [27,29,34,38,44,62,67,69,83,85,91], hospital and/or intensive care unit LOS (n ¼ 10; 8%) [27,34,44,53,65,67,77,83,91], complications (n ¼ 7; 6%) [53e55, 68,72,85], critical care admission (n ¼ 2; 2%) [42,67], and institutionalization (n ¼ 2; 2%) [16,29]. Patient outcomes included sarcopenia (n ¼ 6; 5%) [17,18,24,35,38,93], physical function (n ¼ 5; 4%) [38,57,75,80,93], quality of life (n ¼ 5; 4%) [56,59,64,74,75], falls/fractures (n ¼ 3; 2%) [29,38], frailty (n ¼ 2; 2%)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within healthcare system outcomes, mortality was reported most frequently (n ¼ 33; 27%) [16,22,23,25,26,28e31, 34,37e42,44,45,53,55,57,60,61,65,67,68,73e75,80,83,85,89]. Other outcomes were hospitalization/readmissions/costs (n ¼ 11; 9%) [27,29,34,38,44,62,67,69,83,85,91], hospital and/or intensive care unit LOS (n ¼ 10; 8%) [27,34,44,53,65,67,77,83,91], complications (n ¼ 7; 6%) [53e55, 68,72,85], critical care admission (n ¼ 2; 2%) [42,67], and institutionalization (n ¼ 2; 2%) [16,29]. Patient outcomes included sarcopenia (n ¼ 6; 5%) [17,18,24,35,38,93], physical function (n ¼ 5; 4%) [38,57,75,80,93], quality of life (n ¼ 5; 4%) [56,59,64,74,75], falls/fractures (n ¼ 3; 2%) [29,38], frailty (n ¼ 2; 2%)…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen (23%) studies were retrospective; of these, the types of validity reported were concurrent (n ¼ 1; 7%) [40], concurrent, predictive (n ¼ 2; 14%) [41,57], predictive (n ¼ 10; 71%) [16,26,27,31,34,39,53,68,77,84], and predictive, construct (n ¼ 1; 7%) [32]. Two (14%) studies applied SGA as the semi-gold standard for validation [40,41], and 1 (7%) applied the ESPEN criteria [57].…”
Section: Validation Of Glim Criteriamentioning
confidence: 99%
“…However, previous studies have not validated the accuracy of the SNAQ against the Global Leadership Initiative on Malnutrition (GLIM) criteria, used to diagnose undernutrition in various regions and ethnicities [ 7 ]. The GLIM criteria are highly sensitive in diagnosing undernutrition in older inpatients and have good predictive validity for poor prognosis [ 18 , 19 , 20 , 21 ]. Therefore, determining the sensitivity and specificity of the SNAQ to the GLIM criteria may provide opportunities for interventions for both poor appetite and undernutrition.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous reports indicated a strong correlation between routinely collected data on body weight and the data on body weight measured by standardised methods [ 24 , 25 ]. Moreover, numerous studies that were published recently have reported on real-world (unstandardised) body weight [ 14 , 35 , 36 , 37 , 38 , 39 ]. Thus, the data on body weight reported in our study may be reliable and represent a ‘real-world situation’ that is not fully standardised for body weight measurements.…”
Section: Discussionmentioning
confidence: 99%